RELIABILITY OF LATERAL DISTAL FEMUR DUAL ENERGY X-RAY ABSORPTIOMETRY MEASURES - Mueske, Nicole M. (2013)
Dual-energy x-ray absorptiometry (DXA) of the lateral distal femur (LDF) has been suggested for patients with metal implants or joint contractures preventing DXA scanning at conventional anatomical sites. This study assessed variability in LDF DXA measures due to repeat scanning using data from 5 healthy young adults who had 3 unilateral scans with repositioning between scans. Variability due to image analysis was evaluated in 10 children who underwent bilateral LDF scans with each scan being analyzed 3 times by 2 raters. Regions of interest (ROIs) were defined in the anterior distal metaphysis (R1), metadiaphysis (R2), and diaphysis (R3) as described previously. An additional region (R4) was defined in the metaphysis similar to R1 but centered in the medullary canal. Variability was consistently lower for bone mineral density (BMD) than for bone mineral content (BMC) and bone area; R4 was more repeatable than R1; and variability due to repeat scanning was negligible. These results suggest that DXA measures of the lateral distal femur are reliable and may be useful when standard DXA measures cannot be obtained, but it is recommended that a central, rather than anterior, ROI be used in the metaphysis.